How chitosan-clay-based coatings contribute to improved poly(lactic acid) (PLA) film properties - Rodriguez-Mercado, F; Bruna-Bugueno, J; Torres-Mediano, A (ELSEVIER, 2026)
The feasibility of chitosan and montmorillonite (Cloisite-Na+) coatings as an alternative oxygen barrier material to biodegradable commercial films (polylactic acid, PLA) was investigated. This work aimed at understanding how active chitosan coatings could affect the functional properties of the PLA films. Moreover, chitosan-based coatings also serve as a support for bioactive molecules. The application of these coatings when containing allyl isothiocyanate (AITC) as an antimicrobial agent, is proved as an efficient active releasing system. PLA films were prepared by cast extrusion process and corona treated prior to being coated by chitosan-Cloisite-Na+ suspensions. The incorporation of Cloisite-Na+ and/or AITC into chitosan coating increased the oxygen barrier efficacy of PLA films by almost 10 folds. Indeed, the tortuosity of the diffusion path for oxygen molecules, thanks to the nanoclays dispersion, was highly increased. The water vapor permeability of the coated film was not degraded by the hydrophilic character of the chitosan-based layer. FTIR spectra revealed intermolecular interactions between AITC, chitosan and cloisite explaining the improved properties. The release diffusivity of AITC from the chitosan layer without Cloisite-Na+ was almost 10000 times higher than that of film containing the Cloisite-Na+ at 10%. These active coatings using chitosan is a promising way to improve barrier and functional properties of commercial PLA films.